Adams theorem for the B-Riesz potential in the total B-Morrey spaces - Guliyev, V.S.; Akbulut, A.; Omarova, M.N.; Serbetci, A. (Eurasian Mathematical Journal, 2026)
We prove Adams theorem for the Riesz potential \(I_γ^α\) (B-Riesz potential) in the total Morrey spaces \(L_p,(λ,μ),γ\) (total B-Morrey spaces), associated with the Laplace-Bessel differential operator \(Δ_B\). More precisely, we obtain necessary and sufficient conditions for the operator \(I_γ^α\) to be bounded from the total B-Morrey space \(L_p,(λ,μ),γ\) to the total B-Morrey space \(L_q,(λ,μ),γ\) and from the total B-Morrey space \(L_1,(λ,μ),γ\) to the weak total B-Morrey space \(WL_q,(λ,μ),γ\).